Optimal cut-off value of waist circumference-to-height ratio to predict central obesity in children and adolescents: A systematic review and meta-analysis of diagnostic studies - Eslami, Maysa; Pourghazi, Farzad; Khazdouz, Maryam; Tian, Jing; Pourrostami, Kumars; Esmaeili-Abdar, Zahra; Ejtahed, Hanieh-Sadat; Qorbani, Mostafa (Frontiers in Nutrition, 2023)
Abstract Waist circumference-to-height ratio (WHtR) is a simple anthropometric index with good screening power and fast interpretation for early detection of childhood abdominal obesity. This systematic review and meta-analysis aims to determine the best cut-off value of WHtR to use in clinical setting. Comprehensive searches were conducted in PubMed, Scopus, and Web of Science by the end of March 2021. Observational studies investigated the best WHtR cut-off to detect abdominal obesity in children and adolescents were included. Thirteen articles (n=180,119) were included in this systematic review and eight documents were included in the meta-analysis. The overall optimal cut-off was 0.49 with pooled sensitivity, specificity and diagnostic odds ratio (DOR) of 0.93 (95% confidence interval (CI): 0.93 to 0.96), 0.88 (95% CI: 0.85 to 0.91) and 102.6 (95% CI: 50.7 to 207.5), respectively. The optimal WHtR cut-off to predict abdominal obesity in girls and boys were both 0.49. The current study shows that we could use this cut-off as a simple index for predicting abdominal obesity in children and adolescents without the need for any charts in practice.